Linguistic Tolerance and Intercultural Communication in the Postmodern Era - Ibragimova Feruza Rustamovna; Izatullaev Qasimjan Sabitovich (Uzbekistan Open Conference, 2025)
This article provides a comprehensive analysis of linguistic tolerance as a fundamental condition for successful intercultural communication in the postmodern era. It examines the transformation of communicative processes under the influence of globalization, digitalization, and cultural pluralism. The author explores key contemporary challenges, including linguistic imperialism, communicative egocentrism, and the crisis of linguistic identity. Particular attention is paid to the critical understanding of linguistic discrimination and to identifying practical approaches for creating an inclusive communicative environment based on dialogue and mutual recognition.
Keywords: Linguistic tolerance; intercultural communication; postmodernism; linguistic diversity; linguistic pluralism; communicative strategies; cultural dialogue; linguistic identity; globalization; inclusive communication; linguistic imperialism